2012
DOI: 10.1258/la.2012.012027
|View full text |Cite
|
Sign up to set email alerts
|

Individual housing of female mice: influence on postsurgical behaviour and recovery

Abstract: Individual housing of laboratory mice may increase vulnerability to surgical stress, and interfere with postsurgical recovery. To analyse the effect of housing conditions on recovery, pair-and single-housed female C57BL/6J mice underwent a minor laparotomy þ/2 analgesia, anaesthesia only or no treatment. Animals were monitored using non-invasive methods during the immediate postsurgical period to assess pain and general impairment. While no appearance or posture abnormalities were observed postexperiment, home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 25 publications
(41 reference statements)
2
35
0
Order By: Relevance
“…As observed already in previous studies, 12,13,29 anaesthesia alone had a marked impact on behaviour.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…As observed already in previous studies, 12,13,29 anaesthesia alone had a marked impact on behaviour.…”
supporting
confidence: 86%
“…Even though the motivation to use the nest material was comparable under different conditions, it might be necessary to adapt the scoring system to other nest building material or housing conditions. As social housing is the preferred housing condition for mice and has been suggested to enhance postsurgical recovery in female mice, 15,29,35 further studies should focus on an adaption of the described assessment method to prevalent housing conditions like pair or group housing.…”
mentioning
confidence: 99%
“…Jirkof et al (Jirkof, Cesarovic et al 2012) showed that mice undergoing a mild to moderate impact surgery like a oneside sham embryo transfer, even when not provided with analgesia, did not decrease their water intake post-surgery. Those animals that had been provided with analgesia, on the other hand, increased their water intake post-surgery, at least during the first six hours after surgery (day phase).…”
Section: Discussionmentioning
confidence: 99%
“…All test trials started at 3 pm (lights on) and were digitally recorded for 24h with infrared sensitive cameras in the absence of a human observer. The recorded 24h video material was analysed using the ObserverXT® software (Noldus, Wageningen, Netherlands) (Jirkof et al, 2012).…”
Section: Measurement Of Spontaneous Activitymentioning
confidence: 99%